ANALYSIS OF INDONESIA'S ONE DATA POLICY IMPLEMENTATION IN SUKABUMI REGENCY (CASE STUDY OF THE IMPLEMENTATION OF PRESIDENTIAL REGULATION 39 OF 2019 IN SUKABUMI REGENCY) - Hidayat, Anwar; Saleh, Munandi (Penerbit Lafadz Jaya, 2023)
Satu Data Indonesia is a government data governance policy, to produce quality data so that it can be used for development planning and evaluation. The purpose of this study is to determine the extent of the implementation of Indonesia's One Data policy in Sukabumi Regency. This research uses a descriptive method with a qualitative approach. Data collection techniques through interviews, observations, and documentation studies. The object of his research was a member of the Indonesian Data Source forum in Sukabumi Regency representing 6 informants. Data analysis is carried out through the stages of data collection, data presentation, data reduction, and conclusions. Testing the validity of data uses source, technique, and time triangulation techniques. The results of research on the implementation of Indonesia's one data policy in the Sukabumi Regency have generally been quite effective because policy standards and targets have resulted in changes in the implementation of government data governance in a better direction. In addition, the commitment and attitude of the implementers of this policy are very supportive. The characteristics of the implementing organization One Data Indonesia show that OPD members of the SDI Forum are bureaucracies that obey existing legal regulations. Communication between relevant organizations and SDI policy implementation activities has been going well. The current social, economic, and political environment supports the implementation of SDI policies.